Beyond Diffusion of Improved Technologies to Promoting Innovation Creation and Information Sharing for Increased Agricultural Productivity: A Case Study of Malawi and Kenya - Fallys Masambuka-Kanchewa; Kevan Lamm; Alexa Lamm (Journal of International Agricultural and Extension Education, 2020)
For several decades, various sub-Saharan Africa governments have been proactive in revamping their agricultural extension service delivery systems through establishment and revisions of their agricultural extension policies.Despite the existence and implementation of these policies, productivity in small holder farms in these countries is still low several years later. The need to enhance agricultural production is still cited as a challenge, with low adoption of improved technologies being found as the major contributing factor. This study used a qualitative approach to examine farmers’ perceptions regarding the role of extension agents in the diffusion of innovations and its implications on sustainable agricultural development in Malawi and Kenya. Increased focus on using agricultural extension as an improved technology dissemination tool was found to be one of the factors contributing to low agricultural productivity.This among others was as result of failure by extension to tap valuable information, useful knowledge, skills and resources which was found to be available among farmers in both countries. The findings imply farmers no longer value their local knowledge and areuncomfortable sharing it amongst themselves. However, addressing the challenge of low agricultural productivity (heavily impacted by climate change) in these countries requires a shift in approach when delivering agricultural extension services. These changes include the use of interactive Information and Communication Technologies (ICTs) to solicit feedback and input from farmers and to enhance the two-way communication process
Keywords: diffusion of innovations; extension education; improved technologies; policy